SOCIO-ECONOMIC STRUCTURE AND HOUSEHOLD INCOME DYNAMICS: AN EMPIRICAL STUDY OF THE KAIBARTA COMMUNITY OF HAJO, ASSAM - Das, Jayanta Kr.; Deka, Bandita (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The socio-economic structure of a community refers to its economic and social composition in terms of education, income, occupation, living conditions, age, sex, household size and the resources and opportunities available to its members. Such information is essential for policymakers to design effective public policies aimed at improving overall welfare. In a country like India, it is particularly important for the government and other stakeholders to formulate strategies that enhance the living standards of diverse population groups. Assam is home to various indigenous communities, each contributing to its distinct socio-economic and demographic landscape. The Kaibarta community, one of the major Scheduled Caste groups in Assam, plays a significant role in the state’s socio-economic life. A substantial proportion of this community resides in the Hajo area of Kamrup District of Assam, especially in a locality known as Kaibartatola. This study undertakes a comprehensive socio-economic analysis of the Kaibarta community in Hajo, treating income as the dependent variable. The analysis is based primarily on field-level primary data and examines the influence of key socio-economic parameters on income levels, thereby highlighting the structural factors underlying income distribution within the community. The study is based on primary survey data from 490 households that highlights the structural factors such as land scarcity, poverty, occupational concentration and low human capital, that collectively sustain low income and constrain economic mobility within the community.